Method of preventing irrigation flow deviation and its evaluation during phacoemulsification using dispersive viscoelastic (Viscoblock) in the aspect of the state of the vitreolenticular interface - B.E. Malyugin; A.A. Khaletskaya; O.P. Antonova; D.S. Ostrovskii (Офтальмохирургия)
Purpose. Evaluate state of the vitreolenticular interface before surgery, during phacoemulsification of cataract, and in the early postoperative period. To assess the effectiveness of «Viscoblock» method application during phacoemulsification to prevent intraoperative irrigation fluid misdirection syndrome by blocking the penetration of irrigation fluid through the zonular fibers through injecting dispersive ophthalmic viscosurgical device behind the iris. Material and methods.We operated 49 patients (50 eyes) diagnosed with age-related cataracts. All patients were divided into two groups. In the first group, we performed phacoemulsification with hydrophobic intraocular lens (IOL) implantation and application of the «Viscoblock» method. This group included 24 patients. In the second group, we performed phacoemulsification with hydrophobic IOL implantation using standard technique, it included 25 patients. All patients underwent standard ophthalmological examination and specific additional ones: ultrasound biomicroscopy – UBM Aviso (Quantel Medical, France); spectral optical coherence tomography OCT (Solix, Optovue, USA). Surgical treatment was performed under the control of an operating microscope equipped with intraoperative OCT (Lumera Rescan 700, Carl Zeiss, Germany). Results. According to preoperative diagnostics and it’s UBM data, all patients in the first and second groups showed abnormalities in lens zonular fibers. According to OCT data before the surgery, no cases of anterior hyaloid membrane (AHM) detachment were detected. During the surgery, AHM detachment was observed in 24% of cases in first group and in 56% of cases in second group. Intraoperative iris prolapses occurred in 8% of cases only in the first group. Posterior capsule rupture was observed in only 1 patient in second group. Conclusion. Our technique, «Viscoblock», allows us to limit the penetration of irrigation fluid through the Zonula ciliaris in 76% of cases. However, it should be noted that the method does not provide complete prevention of AHM detachment, as it may already exist in some patients. Additionally, we cannot exclude partial washout of viscoelastic substance during the surgery, which can reduce the tamponade effect.